The role of red coloration and song in peacock spider courtship: insights into complex signaling systems. (8th October 2018) - Girard, Madeline B; Kasumovic, Michael M; Elias, Damian O
Abstract : Peacock-spider males court females using multicolored fans, dances, and songs. We investigated how their showy red fan colors interacted with vibratory songs to affect behavior by manipulating the signaling environment and observing its effects on mating. Contrary to expectation, characteristics of red ornaments and song were not necessary for mating. Instead, our results suggest that females are attending to contrasting patterns on the male fan and not the red colors themselves. Abstract: Research on animal signaling enhances our understanding of links between sensory processing, decision making, behavior, and evolution. Studies of sexually-selected signals may be particularly informative as mate choice provides access to decision patterns in the way that courtship leads to an easily observable behavioral output in choosers, i.e., mating. Male peacock spiders have some of the most elaborate and varied courtship displays known among animals. Particularly striking to human observers is the diversity of red, orange, and yellow ornaments that males exhibit across the genus. The primary objective of our research was to investigate how these visual ornaments interact with vibratory songs to affect female mating behavior of one species, Maratus volans . Accordingly, we conducted mating trials under a series of experimentally manipulated vibratory and lighting conditions. Contrary to expectation, chromatic characteristics of longer wavelength ornaments are not driving female mate choice decisions, despite their extensive presence on male fans. Instead, our results suggest that contrast is important to females. Additionally, we found that vibratory signals were not necessary and did not increase mating rates. Our study demonstrates the intricacies inherent in complex signaling systems.